The empirical evidence on government bond market integration in East Asia - Lian Liu (Journal of East Asian economic integration, 2016)
This research intends to investigate the progress made in East Asian bond market integration thus far. Price-based measures (AAD indicator and beta-convergence measure), quantity-based measures and econometric techniques (co-integration test, error correction model based Granger causality test) are employed in the analysis. Even though East Asian government bond markets have become more integrated since 2001, the differentials among the markets still remain significantly high. The bond market integration process seems slow. The convergence of bond markets sped up in 2003 and after the 2008 world financial crisis, implying the important role of government policies in integrating the regional bond markets. East Asian bond market integration may need more government-directed measures.
10.11644/KIEP.JEAI.2016.20.1.304; 10.11644/KIEP.JEAI.2016.20.1.304; 2718098-0; 2287-8793; Journal of East Asian economic integration; 747208433